Modeling, control and simulation of a small photovoltaic-wind water pumping system without battery bank. (June 2020) - Ferreira, André de Oliveira; Brito, Alaan Ubaiara; Galhardo, Marcos André Barros; Ferreira, Leonam; Macêdo, Wilson Negrão
Abstract: In this work, a small hybrid photovoltaic-wind water pumping system is proposed, modeled and analyzed through computational simulations. In the proposed system, the energy sources are connected via a multi-input DC-DC converter (MIC), whose output is directly connected to a DC motor-pump without using a battery bank. The MIC acts on the sources drained currents simultaneously or individually to operate them at desired points of their characteristic curves. The simulations demonstrate good performance of the system, which it is feasible to be implemented in practice and can be used in remote regions.